Le renforcement de la responsabilité pénale en matière de pollution maritime - Evelyne Monteiro (VertigO, 2010)
After the wreck of Erika and the Prestige, repressive measures concerning the illicit discharges of hydrocarbons from ships were three times modified (laws of May 3rd, 2001, March 9th, 2004 and August 1st, 2008). The sources of this repressive device appearing henceforth to articles L.218-10 and following ones of the Code of the environment are rather complex because they are national, international or they come from Community Law. To give responsibilities the various actors of the sea transport, the Legislator widened the circle of the responsible persons by strengthening considerably the applicable punishments. So, in case of voluntary pollution, the punishments can rise until 10 years of detention and 15 million euro of fine. Moreover, the system is particularly succeeded when the pollution is involuntary because the planned punishments depend on three criteria : The gravity of the fault of committed carelessness, the gravity of the damage caused to the environment and the size of the ship. They can achieve 7 years of detention and 10,5 million euro of fine in the event of an accident of sea aggravated.But this indisputable intensification of the penal responsibility is sometimes done in trompe-l'oeil. Indeed, the repressive device reveals incoherence because of a likely retroactive application of the softer measures of the law of August 1st, 2008 but also the uncertainties of abstract or procedural order. These abnormalities demonstrate the symbolic dimension and not instrumental which takes on too often the criminal law in environmental protection.